Ecotourism Based Revitalization of Urban Riverfront: Design Guideline Framework for the Cikapundung Riverbank, Bandung - Azmi Hibatullah Ramdhani; Hartanto Budiyuwono; Anindhita N. Sunartio (Jurnal Teknik Indonesia, 2026)
Urban rivers in rapidly growing Indonesian cities are frequently marginalized by uncontrolled development, resulting in degraded riparian zones that are ecologically dysfunctional and spatially disconnected from urban life. The study investigates the application of ecotourism principles as a framework for the revitalization of the Cikapundung Riverfront in downtown Bandung, focusing on the abandoned former Palaguna Mall site (±2.5 ha). Through a descriptive qualitative methodology, the research conducts a comparative precedent analysis of the Malacca River (Malaysia) and Cheonggyecheon Stream (South Korea) to derive design criteria across seven urban design dimensions: land use, attraction and character, access and connection, building form and massing, open space, support activities, and preservation. The results suggest that successful riverfront revitalization requires the simultaneous pursuit of sustainable tourism, creative tourism resource development, and dualtrack preservation, both ecological and historical. This evolved guideline framework encourages mixed use zoning with at least 40% blue green open space corridor, pedestrian priority networks with universal accessibility, building heights not exceeding 12 meters within the riverbank zone and adaptive reuse of colonial era heritage structures. The framework provides a replicable model for tropical urban waterfronts across Southeast Asian cities and offers concrete policy recommendations for the Bandung City Government's ongoing revitalization program.